MODELING THE PENETRATION DEPTH DURING LASER MARKING OF LAYERED REINFORCED COMPOSITES WITH A POLYMER MATRIX (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The paper studies the penetration depth of the laser radiation during marking of layered reinforced composite materials with a polymer matrix. The generated radiation is from Fiber laser – RFFL-P-502B. The study of the marking depth was carried out on a measuring microscope using Insize ISD-V150/V250/ V300 software. To derive the mathematical model of the process, a cybernetic scheme with two input factors and one objective function was used. The output power of the laser radiation – P=5÷45W and the marking speed – V=50÷250 mm/s were selected as input quantities. The penetration depth – δ[µm] was the objective function. Based on the derived mathematical models, graphical dependencies in two and three coordinate systems are presented. A dispersion analysis was conducted based on mathematical models and graphical relationships are presented for the influence of the laser beam power and marking speed on the depth of the marking stroke.